Membangun Peradaban: Dinamika Kelembagaan Pendidikan Islam melalui Surau, Masjid, dan Pesantren di Indonesia - Hery Agung Setyawan; moh roqib (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Islamic education in Indonesia has long been an integral part of society, with surau, mosques, and pesantren playing a central role in shaping the character, values, and identity of Muslims. This study uses a qualitative method. The findings show that these three institutions have historically contributed significantly to the formation of Islamic identity, serving as centers for education, moral development, and grounded spiritual values. Over time, they have demonstrated remarkable adaptability through institutional transformation, technological adoption, and the expansion of their social, economic, and educational roles while maintaining core Islamic values. Their contribution to the development of Islamic civilization in Indonesia is substantial, as they continue to produce religious, moderate, and competitive generations and reinforce Islam’s role as a moral and social force in building an inclusive, just, and civilized society.